Life and death in aluminium-exposed cultures of rat lactotrophs studied by flow cytometry - Calejo, Ana I. (2010)
Prolonged exposure to aluminium may impact health. Aluminium's deleterious effects are mostly attributed to its selective accumulation in particular organs and cell types. Occupational exposure to aluminium is allied with a reduced level of serum prolactin, a stress peptide hormone mainly synthesised and secreted by the anterior pituitary lactotrophs. Our aim was to study the effect of aluminium on the viability of rat lactotrophs in primary suspension cultures where multicellular aggregates tend to form, comprising approximately two thirds of the total cell population as confirmed by confocal microscopy. Flow cytometric light scattering of calcein acetoxymethyl ester and ethidium homodimer-1 labelled cells was used to define subpopulations of live and dead cells in heterogeneous suspensions comprised of single cells and multicellular aggregates of distinct size. Concentration-dependent effects of AlCl(3) were observed on aggregate size and cell survival. After 24-h exposure to 3 mM AlCl(3), viability of single cells declined from 5% to 3%, while in multicellular aggregates, viability declined from 23% to 20%. The proportion of single cells increased from 30% to 42% within the same concentration range, while in large aggregates, the proportion remained approximately constant representing 35% of the cell suspension. In large aggregates, cell viability (75%) remained unaltered after exposure to AlCl(3) concentrations up to 300 mu M, while in single cells, viability was halved at 30 mu M. In conclusion, our finding indicates that prolonged exposure to aluminium may lead to significant loss of pituitary cells.